2021
DOI: 10.1016/j.ijid.2021.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Comparative diagnostic performance of rapid antigen detection tests for COVID-19 in a hospital setting

Abstract: Background: The availability of accurate and rapid diagnostic tools for COVID-19 is essential for tackling the ongoing pandemic. Our study aimed to quantify the performance of available antigen-detecting rapid diagnostic tests (Ag-RDTs) in a real-world hospital setting. Methods: In this retrospective analysis, the diagnostic performance of 7 Ag-RDTs was compared with realtime reverse transcription quantitative polymerase chain reaction assay in terms of sensitivity, specificity and expected predictive values. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…The HG COVID assay satisfies these criteria. An assessment of several Ag-RDTs recently performed at our laboratory [27] showed overall sensitivity of 78.7% (95% CI: 73.2-83.3%); this, however, varied significantly by Ct value and brand. We concluded that Ag-RDTs are convenient for screening purposes in moderate-to-high intensity settings [27].…”
Section: Discussionmentioning
confidence: 88%
“…The HG COVID assay satisfies these criteria. An assessment of several Ag-RDTs recently performed at our laboratory [27] showed overall sensitivity of 78.7% (95% CI: 73.2-83.3%); this, however, varied significantly by Ct value and brand. We concluded that Ag-RDTs are convenient for screening purposes in moderate-to-high intensity settings [27].…”
Section: Discussionmentioning
confidence: 88%
“…The HG COVID assay satis es these criteria. An assessment of several Ag-RDTs recently performed at our laboratory [30] showed overall sensitivity of 78.7% (95% CI: 73.2-83.3%); this, however, varied signi cantly by Ct value and brand. We concluded that Ag-RDTs are convenient for screening purposes in moderate-to-high intensity settings [30].…”
Section: Discussionmentioning
confidence: 89%
“…An assessment of several Ag-RDTs recently performed at our laboratory [30] showed overall sensitivity of 78.7% (95% CI: 73.2-83.3%); this, however, varied signi cantly by Ct value and brand. We concluded that Ag-RDTs are convenient for screening purposes in moderate-to-high intensity settings [30]. In the present study, the analytical performance of the HG COVID-19 assay was comparable to that of RT-PCR; the assay may therefore be an alternative molecular diagnostic tool for SARS-CoV-2 detection, independently of the purpose and the viral epidemiology.…”
Section: Discussionmentioning
confidence: 89%
“…155 Bruzzone et al have quantified the performance of seven different available types of antigendetecting rapid diagnostic tests compared with RT-qPCR, and the results showed that the overall sensitivity and specificity of antigen tests were 78.7% and 100%, respectively, and a wide range of sensitivity of different brands (66.0-93.8%) was observed. 156 Therefore, further investigations and confirmatory studies are needed for the validation of different antigendetection kits.…”
Section: Antigen Testingmentioning
confidence: 99%